Beyond Open Access: Conceptualizing Open Science for Knowledge Co-creation - Mačiulienė, Monika (Frontiers in Communication, 2022)
Despite the calls from European Union (EU) and global institutions, such as UNESCO and Organization for Economic Co-operation and Development (OECD) for more openness and collaboration between Quadruple Helix actors (government, academia, industry, and civil society), in practice, scientific knowledge creation has been much more closed and fragmented. As an emerging field of study, Open Science (OS) for knowledge co-creation currently requires significantly conceptual and theoretical challenges to be addressed before advancing to practical application. To address this gap, the paper aims to develop a conceptual framework integrating diverse understandings of OS beyond the use of Open Access (OA) and data practices. The author argues that OS should be approached as a complex ecosystem with the potential for knowledge co-creation and social innovations. The underlying premise of the proposed conceptual model is the interdisciplinarity in integrating multiple reference disciplines. Such an approach allows us to learn from other disciplines and contribute to OS research through the emergence of new ideas for theory and practical application. Consequently, a dyadic model is presented where (1) framework conditions regulate how (2) systemic conditions can realize their full potential for knowledge co-creation resulting in outputs (e.g., collaborative projects and citizen science projects) and outcomes (e.g., social innovations, higher quality of science, and democratized knowledge) beneficial for a broad spectrum of stakeholders.